Day 3 Wed, October 02, 2013 2013
DOI: 10.2118/166380-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Well Modeling of Liquid-Rich Shale Reservoirs

Abstract: This paper presents an integrated modeling approach for history matching and economic optimization of wells producing from liquid-rich shale reservoirs (LRSR). History matching uses daily pressures and gas-oil-water production data to estimate average parameters in a 2D/3D finite-difference (FD) horizontal multi-fractured well model: rock permeability, fracture halflength, relative permeabilities, and in-situ fluid (solution gas-oil ratio). Economic-based well design uses the same FD model to maximize net pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The wellbore flowing pressure will be lower than the dew point pressure. Juell and Whitson (2013) did simulation work to find optimal operation conditions for gas condensate shale reservoirs in the depletion mode. They found that the optimal production strategy for wells producing from highly undersaturated gas condensate reservoirs is likely to have an initial period where the flowing pressure equals the saturation pressure, followed by a gradual increase in drawdown, towards the minimum bottom-hole pressure that is operationally possible.…”
Section: Gas Injection In Gas Condensate Reservoirsmentioning
confidence: 99%
“…The wellbore flowing pressure will be lower than the dew point pressure. Juell and Whitson (2013) did simulation work to find optimal operation conditions for gas condensate shale reservoirs in the depletion mode. They found that the optimal production strategy for wells producing from highly undersaturated gas condensate reservoirs is likely to have an initial period where the flowing pressure equals the saturation pressure, followed by a gradual increase in drawdown, towards the minimum bottom-hole pressure that is operationally possible.…”
Section: Gas Injection In Gas Condensate Reservoirsmentioning
confidence: 99%
“…SP models typically assume each hydraulic fracture unit is identical, so only a single unit must be modeled, and simple scale-up can be applied (e.g. Juell and Whitson, 2013).…”
Section: Reservoir Simulation -Well History Matching (Hm)mentioning
confidence: 99%